2013
DOI: 10.1021/om400143u
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Deprotonation of a Thiol-Functionalized Bis(1,2,4-triazolium) Salt as a Selective Route to Heterometallic NHC Complexes

Abstract: Heterometallic NHC complexes have been selectively prepared at room temperature directly from an azolium salt in a two-step procedure. In the unsymmetrically substituted bis(1,2,4-triazolium) ligand precursor, one of the m-xylylene-bridged triazolium units features an unprotected o-thiophenol substituent. This renders possible a selective deprotonation and in situ monopalladation at the NHC−thiolato unit. The obtained palladium(II) complex possesses two pendant triazolium units as vacant binding sites. After a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The complexes containing M C and the other metal usually exist as the intermediates rapidly involved in the intramolecular transmetalation. However, certain examples have shown that the heterometallic NHC-M C complexes formed during the treatment of the corresponding metalcontaining imidazolium salts with Ag 2 O [152][153][154][155][156][157] or Cu 2 O [115] are stable and can be isolated. The similar heterometallic NHC-M C complexes (pre-synthesized or generated in situ) can be involved in the transmetalation reaction at the M C atom with preservation of the other metal coordinated at the neighbor covalently bound ligand (Scheme 30) [114,115,[158][159][160][161][162][163][164][165][166][167][168][169][170][171][172].…”
Section: Transmetalation Retaining the Other Atom In The Productmentioning
confidence: 99%
“…The complexes containing M C and the other metal usually exist as the intermediates rapidly involved in the intramolecular transmetalation. However, certain examples have shown that the heterometallic NHC-M C complexes formed during the treatment of the corresponding metalcontaining imidazolium salts with Ag 2 O [152][153][154][155][156][157] or Cu 2 O [115] are stable and can be isolated. The similar heterometallic NHC-M C complexes (pre-synthesized or generated in situ) can be involved in the transmetalation reaction at the M C atom with preservation of the other metal coordinated at the neighbor covalently bound ligand (Scheme 30) [114,115,[158][159][160][161][162][163][164][165][166][167][168][169][170][171][172].…”
Section: Transmetalation Retaining the Other Atom In The Productmentioning
confidence: 99%
“…( F ) Copper catalyzed diarylation of 3-mercaptotriazole [ 45 ]. ( G ) Oxidation of benzothiazolotriazolium salts to N -substituted benzothiazolotriazolium derivatives [ 46 , 47 ]. ( H ) This work: Synthesis of benzothiazolotriazole derivatives via C-H bond functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…A third approach leading to the benzo[4,5]thiazolo[2,3- c ][1,2,4]triazole ring system is based on forming the thiazole ring in the last reaction step by a bond formation between the sulfur of the 2-mercaptophenyl substituent of a triazole and the unfunctionalized triazole carbon ( Scheme 1 G,H). The Straub group has observed two of their thiol-containing triazolium salts ( X ) undergo an oxidative cyclization in DMSO ( Scheme 1 G), thereby forming charged N -substituted heteroaromatic compounds, Y [ 46 , 47 ]. As opposed to the acidic triazolium starting materials of the Straub group, we demonstrate in this report that a similar bond formation can be employed to obtain neutral benzo[4,5]thiazolo[2,3- c ][1,2,4]triazoles containing a wide variety of functional groups on the benzene ring from non-acidic triazoles ( Scheme 1 H).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Nowadays, NHCs are considered to be maturel igands and are widely used in transition metal and main group chemistry. [13][14][15][16] In this way,f urtherd onor sites such as phosphines, [17][18][19][20][21] alcohols, [22][23][24][25] thiols, [26,27] and other functional groups [28][29][30] can be combined with NHC chemistry and allow ab road variety of applicationsf or functionalized NHC complexes. [13][14][15][16] In this way,f urtherd onor sites such as phosphines, [17][18][19][20][21] alcohols, [22][23][24][25] thiols, [26,27] and other functional groups [28][29][30] can be combined with NHC chemistry and allow ab road variety of applicationsf or functionalized NHC complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Besides their different steric ande lectronic properties compared to, for example, phosphines, NHCs are easily functionalized, as almosta ny organic substituent can be attached to the nitrogen atoms. [13][14][15][16] In this way,f urtherd onor sites such as phosphines, [17][18][19][20][21] alcohols, [22][23][24][25] thiols, [26,27] and other functional groups [28][29][30] can be combined with NHC chemistry and allow ab road variety of applicationsf or functionalized NHC complexes. Besides their applicationi nc atalysis, coinage metal compounds have also been extensively investigatedw ith respect to their photoluminescence properties.…”
Section: Introductionmentioning
confidence: 99%